2008
DOI: 10.1121/1.2934376
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of impulse-like sources to be used in reverberation time measurements

Abstract: an impulse-like source that will comply with certain demands concerning its spectral content and sound pressure levels it can provide. Although the relevant standards state that such kind of sources should be avoided due to the lack of measurement repeatability, their use has proved to be necessary due to inability of conventional omnidirectional loudspeakers to provide adequate sound pressure levels, especially at the low end of the frequency range of interest, thereby ensuring sufficient dynamic range. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…Regarding frequency response, the balloon does not offer adequate excitation at the low frequencies [68]. The spectral content of balloon bursts clearly indicates the direct relation between balloon size and the overall spectrum.…”
Section: Balloonmentioning
confidence: 97%
See 4 more Smart Citations
“…Regarding frequency response, the balloon does not offer adequate excitation at the low frequencies [68]. The spectral content of balloon bursts clearly indicates the direct relation between balloon size and the overall spectrum.…”
Section: Balloonmentioning
confidence: 97%
“…Relating to sound pressure levels, Horvat et al [68] measured differed sized balloons and found levels ranging from 133 to 138 dB. Results from Pätynen et al [67] ranged from 121 to 137.5 dB.…”
Section: Balloonmentioning
confidence: 99%
See 3 more Smart Citations